1999
DOI: 10.1074/jbc.274.49.34584
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides Activate Cultured Rat Brain Microglia

Abstract: Microglia, brain resident macrophages, are activated in brain injuries and several neurodegenerative diseases. However, microglial activators that are produced in the brain are not yet defined. In this study, we showed that gangliosides, sialic acid-containing glycosphingolipids, could be a microglial activator. Gangliosides induced production of nitric oxide (NO) and tumor necrosis factor-␣ (TNF-␣) and expression of cyclooxygenase-2 (COX-2). The effect of gangliosides on NO release increased dose-dependently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
4

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 53 publications
9
118
4
Order By: Relevance
“…In our previous studies with cultured rat primary microglia (Jou et al, 2006;Kim et al, 2002;Pyo et al, 1999), we observed that brain gangliosides mixture (Gmix) induced morphological changes in cultured rat primary microglia which were different from those induced by other agents such as LPS or IFN-γ. Therefore, to further pursue this observation, we plated cultured rat primary microglia onto 35 mm dishes, incubated them with either Gmix (50 μg/ml), LPS (100 ng/ml), or IFN-γ (10 U/ml) for 3 days, and observed morphological changes using phasecontrast microscopy.…”
Section: 1mentioning
confidence: 97%
See 2 more Smart Citations
“…In our previous studies with cultured rat primary microglia (Jou et al, 2006;Kim et al, 2002;Pyo et al, 1999), we observed that brain gangliosides mixture (Gmix) induced morphological changes in cultured rat primary microglia which were different from those induced by other agents such as LPS or IFN-γ. Therefore, to further pursue this observation, we plated cultured rat primary microglia onto 35 mm dishes, incubated them with either Gmix (50 μg/ml), LPS (100 ng/ml), or IFN-γ (10 U/ml) for 3 days, and observed morphological changes using phasecontrast microscopy.…”
Section: 1mentioning
confidence: 97%
“…We previously reported that Gmix activates JAK-STAT and MAPK signaling pathways in rat primary microglia (Kim et al, 2002;Pyo et al, 1999). Therefore, to elucidate whether JAK-STAT and MAPK signaling pathways are involved in the ramified morphological changes in GM1-treated rat primary microglia, microglial cells were preincubated with either Jaki (a selective inhibitor of Jak), PD98059 (a selective inhibitor of Erk1/2), SB203580 (a selective inhibitor of p38), or SP600125 (a selective inhibitor of JNK), and were then incubated with GM1 for 3 days.…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…We next investigated whether IL-13 could induce cell death of microglia that had been treated with other activators, namely ganglioside and thrombin (Pyo et al, 1999;Ryu et al, 2000). In response to the combination of ganglioside mixture (Gmix) and IL-13, 29.4% Ϯ 13.5%, 42.9% Ϯ 6.7%, and 80.0% Ϯ 7.4% of total cells were Etd-1-positive at day 4, 5, and 6, respectively ( Fig.…”
Section: Il-13 Induced Cell Death Of Activated Microgliamentioning
confidence: 99%
“…Therefore, like LPS, Gmix also induced microglial cell death in the presence of IL-13, but Gmix alone did not induce cell death, even after 6 days. We also compared the effect of GT1b and GM1 on microglial cell death since GT1b is an active component of Gmix that induces microglial activation, while GM1 does not have such activity (Pyo et al, 1999). The data presented in Figure 2B show that at day 5, 54.6% Ϯ 10.4% of cells treated with GT1b and IL-13 were Etd-1-positive, while only 5.2% Ϯ 2.7% of cells treated with GM1 and IL-13 were Etd-1-positive.…”
Section: Il-13 Induced Cell Death Of Activated Microgliamentioning
confidence: 99%